The association between the severity and distribution of white matter lesions and hemorrhagic transformation after ischemic stroke: A systematic review and meta-analysis - Wang, Youjie; Bai, Xueling; Ye, Chen; Yu, Yifan; Wu, Bo (Frontiers in Aging Neuroscience, 2022)
Background and purpose As a part of the natural course of ischemic stroke, hemorrhagic transformation (HT) is a serious complication after reperfusion treatment, which may affect the prognosis of patients with ischemic stroke. White matter lesions (WMLs) refer to focal lesions on neuroimaging and have been suggested to indicate a high risk of HT. This systematic review and meta-analysis aimed to summarize current evidence on the relation between WML and HT. Methods This systematic review was prepared with reference to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We searched PubMed, Embase, Web of Science, and Cochrane Library databases for publications on WML and HT in patients with ischemic stroke. Odds ratios (ORs) and 95% confidence intervals (CIs) from eligible studies were combined to quantify the association between the severity of WML and the risk of HT. In addition, the descriptive analysis was adopted to evaluate the influence of different WML distributions on predicting HT. Results A total of 2,303 articles were identified after removing duplicates through database searching, and 41 studies were included in our final analysis. The meta-analysis showed that the presence of WML was associated with HT (OR = 1.62, 95%CI 1.08–2.43, p = 0.019) and symptomatic intracerebral hemorrhage (sICH) (OR = 1.64, 95%CI 1.17–2.30, p = 0.004), and moderate-to-severe WML indicated a high risk of HT (OR = 2.03, 95%CI 1.33–3.12, p = 0.001) and sICH (OR = 1.92, 95%CI 1.31–2.81, p < 0.001). The dose–response meta-analysis revealed risk effects of increasing the severity of WML on both HT and ICH. In addition, both periventricular WML (PWML) (five of seven articles) and deep WML (DWML) (five of six articles) were shown to be associated with HT. Conclusions White matter lesions are associated with overall HT and sICH in patients with ischemic stroke, and more severe WMLs indicate a high risk of HT and sICH. In addition, both PWML and DWMLs could be risk factors for HT. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier: PROSPERO CRD42022313467.